PELATIHAN METODE CLICKBAIT DALAM PERIKLANAN MEDIA SOSIAL FACEBOOK SEBAGAI SOLUSI JUAL BELI ONLINE DI DESA NAPIS KECAMATAN TAMBAKREJO KABUPATEN BOJONEGORO - Nur Dwi Sukmono; Rina Puji Rahayu (STKIP Citra Bakti, 2022)
The purpose of this training is to upgrade public understanding of the online market at the same time can compete in online advertising. Through the clickbait method, it is hoped that the public will be able to understand the development pattern of online advertising and be able to apply it for the benefit of buying and selling. This Community Service activity was carried out in Napis Village, Tambakrejo District, Bojonegoro Regency with training and mentoring methods. The materials in this training include making headlines and sub-headlines, body copy, and legal offer limitation. The training participants totaled 46 people consisting of 22 micro, small and medium enterprises, 13 students, and 11 housewives as well as small traders. Training on making clickbait ads for Facebook social media can be a solution in dealing with the new normal. Judging from the average mastery of the material of 83.4, it shows that participants are able to create clickbait ads.